Practical recommendations to avoid physical deconditioning during confinement due to pandemic associated with COVID-19 - Mera-Mamián, Andry Yasmid; Tabares-Gonzalez, Esteban; Montoya-Gonzalez, Santiago; Muñoz-Rodriguez, Diana Isabel; Monsalve Vélez, Felipe (Universidad y Salud, 2020)
Introduction: Social isolation during the COVID-19 pandemic includes home confinement, which results in increased physical inactivity and sedentary behaviors, favoring physical deconditioning. Deconditioned people have metabolic and systemic disorders due to the lack of movement. Objective: To present practical, low-cost recommendations on evidence-based activities to avoid physical deconditioning during home confinement, which can be maintained over the long term, even after the pandemic. Materials and methods: Documentary review on strategies to support healthy lifestyles at home that decrease the negative effects at a physiological level produced by the confinement derived from the pandemic. Results: Evidence indicates that home confinement increases the levels of physical inactivity and sedentary behavior; executing physical activity under particular conditions, among other effects, can strengthen the respiratory and immune systems, maintain physical condition and generate positive effects on mental health. Conclusions: The habits related to the practice of physical activity at home should be maintained over time, it is recommended to do it on a scheduled basis, define rest times between activities and during the night, and choosing those that generate enjoyment.